An Atopic Dermatitis Management Algorithm for Primary Care Providers and Assessment of Its Usefulness as a Clinical Tool. Issue 4 (25th May 2017) - Miyar, Maria E.; Brown, Megan; Vivar, Karina L.; Jablon, Kimberly; Boscardin, Christy; Levy, Moise L.; Teng, Joyce M.; Mathes, Erin F.
Abstract: Background/Objectives: There is a lack of primary care provider (PCP) understanding of atopic dermatitis (AD) treatments and topical steroid use. We designed an AD management algorithm for pediatric PCPs. We hypothesized that the algorithm would improve pediatric PCPs' knowledge of AD diagnosis and management. Methods: Pediatric primary care resident and attending physicians at three residency programs were invited to participate in an electronic AD algorithm survey that contained demographic and 19 knowledge‐based questions. Participants were randomized to intervention and control groups, with the intervention group receiving a short lecture and copy of our algorithm to use in an inpatient or outpatient setting for 2 months. Changes in scores between preintervention and postintervention surveys were compared. Results: Of the 54 participants, those in the intervention group ( n = 26) performed significantly better than those in the control group ( n = 28) after controlling for pretest scores (β = 1.19 [95% confidence interval 0.07, 2.32], p = 0.04). The intervention group had a higher average score on the posttest knowledge questions (71% correct) than the control group (65% correct) (p = 0.06). The majority of physicians who received the algorithm agreed or strongly agreed that they liked using the algorithm. Conclusion: The use of a management algorithm improved physician knowledge about the diagnosis and treatment of AD and was well accepted by physicians. Use of this management algorithm may lead to better recognition and management of AD, particularly earlier recognition of and therapy for superinfection, improving treatment outcomes and quality of life for patients and families.